Optimally resilient codes for list-decoding from insertions and deletions - Venkatesan Guruswami; Bernhard Haeupler; Amirbehshad Shahrasbi (2020)
We give a complete answer to the following basic question: "What is the maximal fraction of deletions or insertions tolerable by q-ary list-decodable codes with non-vanishing information rate?"